COMMUNICATION STRATEGY CONTENT PLANNER ON RBTV YOGYAKARTA SOCIAL MEDIA TEAM - Erlistyarini, Yulinda; Kiki Astria, Kadek (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
The purpose of this study was to analyze the communication strategy of the content planner on the RBTV Yogyakarta social media team. This study uses a constructivism paradigm with an analytical qualitative method approach. Data analysis uses the results of interviews, observations and supporting documents. Using the theory of communication strategy from Wayne Pace which states that communication strategy has three objectives including to secure understanding, to establish acceptance, and to motivate action. The results of the study are that the communication strategy carried out by the RBTV social media team has clear stages to achieve content success, the RBTV social media team uses stages such as setting content goals, mapping target markets, content idea planning strategies, and evaluation.